Autophagy in age-related macular degeneration. Issue 2 (1st February 2023) - Kaarniranta, Kai; Blasiak, Janusz; Liton, Paloma; Boulton, Michael; Klionsky, Daniel J.; Sinha, Debasish
ABSTRACT: Age-related macular degeneration (AMD) is the leading cause of visual impairment in the aging population with limited understanding of its pathogenesis and a lack of effective treatment. The progression of AMD is initially characterized by atrophic alterations in the retinal pigment epithelium, as well as the formation of lysosomal lipofuscin and extracellular drusen deposits. Damage caused by chronic oxidative stress, protein aggregation and inflammatory processes may lead to geographic atrophy and/or choroidal neovascularization and fibrosis. The role of macroautophagy/autophagy in AMD pathology is steadily emerging. This review describes selective and secretory autophagy and their role in drusen biogenesis, senescence-associated secretory phenotype, inflammation and epithelial-mesenchymal transition in the pathogenesis of AMD. Abbreviations: Aβ: amyloid-beta; AMBRA1: autophagy and beclin 1 regulator 1; AMD: age-related macular degeneration; ATF6: activating transcription factor 6; ATG: autophagy related; BACE1: beta-secretase 1; BHLHE40: basic helix-loop-helix family member e40; BNIP3: BCL2 interacting protein 3; BNIP3L/NIX: BCL2 interacting protein 3 like; C: complement; CALCOCO2/NDP52: calcium binding and coiled-coil domain 2; CARD: caspase recruitment domain; CDKN2A/p16: cyclin dependent kinase inhibitor 2A; CFB: complement factor B; DELEC1/Dec1; deleted in esophageal cancer 1; EIF2AK3/PERK: eukaryotic translation initiation factor 2 alpha kinase 3; EMT: epithelial-mesenchymal transition; ER: endoplasmic reticulum; ERN1/IRE1: endoplasmic reticulum to nucleus signaling 1; FUNDC1: FUN14 domain containing 1; GABARAP: GABA type A receptor-associated protein; HMGB1: high mobility group box 1; IL: interleukin; KEAP1: kelch like ECH associated protein 1; LAP: LC3-associated phagocytosis; LAMP2: lysosomal associated membrane protein 2; LIR: LC3-interacting region; MAP1LC3/LC3: microtubule associated protein 1 light chain 3; MTOR: mechanistic target of rapamycin kinase; NFE2L2: NFE2 like bZIP transcription factor 2; NLRP3; NLR family pyrin domain containing 3; NFKB/NFκB: nuclear factor kappa B; OPTN: optineurin; PARL: presenilin associated rhomboid like; PGAM5: PGAM family member 5, mitochondrial serine/threonine protein phosphatase; PINK1: PTEN induced kinase 1; POS: photoreceptor outer segment; PPARGC1A: PPARG coactivator 1 alpha; PRKN: parkin RBR E3 ubiquitin protein ligase; PYCARD/ASC: PYD and CARD domain containing; ROS: reactive oxygen species; RPE: retinal pigment epithelium; SA: secretory autophagy; SASP: senescence-associated secretory phenotype; SEC22B: SEC22 homolog B, vesicle trafficking protein; SNAP: synaptosome associated protein; SNARE: soluble N-ethylmaleimide-sensitive factor attachment protein receptor; SQSTM1/p62: sequestosome 1; STX: syntaxin; TGFB2: transforming growth factor beta 2; TRIM16: tripartite motif containing 16; TWIST: twist family bHLH transcription factor; Ub: ubiquitin; ULK: unc-51 like autophagy activating kinase; UPR: unfolded protein response; UPS: ubiquitin-proteasome system; V-ATPase: vacuolar-type H + -translocating ATPase; VIM: vimentin